Implementation of Rain-Fed Reservoirs as an Agricultural Irrigation Solution in Kedungbenda Purbalingga Village: Penerapan Embung Tadah Hujan sebagai Solusi Irigasi Pertanian di Desa Kedungbenda Purbalingga - Sudianto; Reni Dyah Wahyuningrum; Ajeng Dyah Kurniawati (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Kedungbenda Village, Purbalingga Regency, has great agricultural potential. Agriculture in Kedungbenda Village is the livelihood of most of the village population. However, the